2017
DOI: 10.1186/s12872-017-0622-2
|View full text |Cite
|
Sign up to set email alerts
|

Major adverse cardiac events and mortality in chronic obstructive pulmonary disease following percutaneous coronary intervention: a systematic review and meta-analysis

Abstract: BackgroundWe aimed to systematically compare Major Adverse Cardiac Events (MACEs) and mortality following Percutaneous Coronary Intervention (PCI) in patients with and without Chronic Obstructive Pulmonary Diseases (COPD) through a meta-analysis.MethodsElectronic databases (Cochrane library, EMBASE and Medline/PubMed) were searched for English publications comparing in-hospital and long-term MACEs and mortality following PCI in patients with a past medical history of COPD. Statistical analysis was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In a systematic review and meta-analysis of 10 studies (7518 patients with COPD and 65,451 patients without COPD), a comparison of major adverse cardiac events (MACEs) and mortality following percutaneous coronary intervention revealed that in-hospital (OR 1.40, 95% CI 1.19-1.65; P = 0.001) and long-term MACEs (OR 1.58, 95% CI 1.38-1.81, P = 0.001) were significantly higher in patients with COPD. 62 Therefore, COPD should be considered a risk factor for the development of adverse clinical outcomes following coronary revascularization procedures. Regrettably, in all of these studies, definition of COPD is based in the clinical history or discharge codes, without spirometric confirmation and underdiagnosis of COPD in IHD is about 80%.…”
Section: Systematic Reviews and Meta-analysismentioning
confidence: 99%
“…In a systematic review and meta-analysis of 10 studies (7518 patients with COPD and 65,451 patients without COPD), a comparison of major adverse cardiac events (MACEs) and mortality following percutaneous coronary intervention revealed that in-hospital (OR 1.40, 95% CI 1.19-1.65; P = 0.001) and long-term MACEs (OR 1.58, 95% CI 1.38-1.81, P = 0.001) were significantly higher in patients with COPD. 62 Therefore, COPD should be considered a risk factor for the development of adverse clinical outcomes following coronary revascularization procedures. Regrettably, in all of these studies, definition of COPD is based in the clinical history or discharge codes, without spirometric confirmation and underdiagnosis of COPD in IHD is about 80%.…”
Section: Systematic Reviews and Meta-analysismentioning
confidence: 99%
“…COPD is a common comorbidity in patients with chronic cardiac diseases and contributes to poor outcomes including increased mortality following cardiac procedures 6‐11 . Its role in mitral valve periprocedural complications has been seldom studied.…”
Section: Discussionmentioning
confidence: 99%
“…COPD is a common comorbidity in patients with chronic cardiac diseases and contributes to poor outcomes including increased mortality following cardiac procedures. [6][7][8][9][10][11] Its role in mitral valve periprocedural complications has been seldom studied. One small, prospective observational study showed COPD to be an independent predictor of composite mortality, cardiac re-hospitalization, re-intervention, and major cerebro-vascular and cardiac events.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 Patient was considered adherent in case there was no evidence of randomized treatment discontinuation prior to follow-up visits scheduled at 30 days, 3, 6, 12, 18, and 24 months after the index procedure 9,10 (Supplementary material online, Appendix per-protocol restart of DAPT allowed: (i) ticagrelor and aspirin for 30 days in the experimental treatment strategy group, (ii) DAPT with ticagrelor and aspirin (ACS, stable CAD patients already on ticagrelor or prasugrel), clopidogrel and aspirin (stable CAD) for 365 days in the standard treatment strategy group. 1…”
Section: Patient Populationmentioning
confidence: 99%
“…Patients with coronary artery disease (CAD) and chronic obstructive pulmonary disease (COPD) represent a population at increased risk for adverse clinical events, periprocedural complications, comorbidities, and polypharmacy. [1][2][3] In PLATO, dual antiplatelet therapy (DAPT) consisting of ticagrelor and aspirin reduced the composite primary endpoint of cardiovascular death, myocardial infarction (MI), or stroke in patients with acute coronary syndromes (ACS), compared with clopidogrel and aspirin. However, ticagrelor increased the incidence of dyspnoea, which may lead clinicians to withhold ticagrelor from COPD patients.…”
Section: Introductionmentioning
confidence: 99%